Proteostasis is essential during cochlear development for neuron survival and hair cell polarity. (19th July 2019) - Freeman, Stephen; Mateo Sánchez, Susana; Pouyo, Ronald; Van Lerberghe, Pierre‐Bernard; Hanon, Kevin; Thelen, Nicolas; Thiry, Marc; Morelli, Giovanni; Van Hees, Laura; Laguesse, Sophie; Chariot, Alain; Nguyen, Laurent; et al.
Abstract: Protein homeostasis is essential to cell function, and a compromised ability to reduce the load of misfolded and aggregated proteins is linked to numerous age‐related diseases, including hearing loss. Here, we show that altered proteostasis consequent to Elongator complex deficiency also impacts the proper development of the cochlea and results in deafness. In the absence of the catalytic subunit Elp3, differentiating spiral ganglion neurons display large aggresome‐like structures and undergo apoptosis before birth. The cochlear mechanosensory cells are able to survive proteostasis disruption but suffer defects in polarity and stereociliary bundle morphogenesis. We demonstrate that protein aggregates accumulate at the apical surface of hair cells, where they cause a local slowdown of microtubular trafficking, altering the distribution of intrinsic polarity proteins and affecting kinocilium position and length. Alleviation of protein misfolding using the chemical chaperone 4‐phenylbutyric acid during embryonic development ameliorates hair cell polarity in Elp3‐deficient animals. Our study highlights the importance of developmental proteostasis in the cochlea and unveils an unexpected link between proteome integrity and polarized organization of cellular components. Synopsis: Loss of the Elongator subunit Elp3 in the inner ear results in enhanced protein misfolding and aggregation. Impaired proteostasis negatively affects neuron survival and sensory cell polarity and results in deafness. Aggresome‐like structures are found in Elongator‐deficient cells. Embryonic spiral ganglion neurons (SGNs) depend on Elongator and proteostasis for survival. Cochlear hair cells (HCs) depend on Elongator and proteostasis for appropriate localization of the kinocilium and stereociliary bundle. Accumulation of misfolded protein aggregates in HEK293T and cochlear HCs reduces microtubular transport and affects the distribution of LGN polarity protein. Abstract : Loss of the Elongator subunit Elp3 in the inner ear results in enhanced protein misfolding and aggregation. Impaired proteostasis negatively affects neuron survival and sensory cell polarity and results in deafness.